The Mediating Effect of Green Motivation between GHRM and Voluntary Green Behavior in Indonesia's Companies and Organizations - Sanjaya, Nicolaus Bayu; Edastama, Primasatria (Universitas Muhammadiyah Yogyakarta, 2025)
Research aims: The goal of this study is to investigate the impact of GHRM on VGB, which can be influenced by a variety of factors, including employee green motivation (GM). This study also uses environmental belief (EB) as a mediation that affects GHRM on VGB and green organizational identity (GOI) as a mediation that affects GHRM on TGB.Design/Methodology/Approach: The design implemented is quantitative research that utilizes Structural Equation Modeling (SEM) with Confirmatory Factor Analysis (CFA) as the method of analysis. The sampling method used is purposive sampling, with a minimum of 135 respondents who are employees or members of organizations in Indonesia that implement an environmentally friendly culture and are at least 21 years old. This design is consistent with the characteristics of SEM-CFA research, which tests hypotheses and confirms correlations between observable and latent variables.Research findings: The study found that GHRM improves employees' voluntary and task related green behaviors. Environmental beliefs and the identity of eco-friendly organizations serve as crucial mediators in this relationship. GHRM also influences green motivation, although it does not directly drive green behavior. These findings highlight the importance of environmentally friendly HR policies in supporting employee behavior and improving the company's environmental performance.Theoretical Contribution/Originality: This study provides a theoretical contribution by demonstrating how Green Human Resource Management (GHRM) influences employees' green behavior through factors such as environmental belief (EB) and green organizational identity (GOI). Practically, this research emphasizes the importance of a more comprehensive implementation of Green Human Resource Management to enhance employees' green behavior and the environmental performance of companies in Indonesia.Practitioners/Policy Implications: The implication for building VGB and TGB is that employees need to implement GHRM practices optimally so that their EB and GOI can be effectively carried out, thereby positively impacting VGB and TGB.Research Limitations/Implications: The limitations of this study include its focus on companies in Indonesia, making the results less generalizable to other countries. The incomplete implementation of GHRM limits the findings on the impact of green motivation (GM) on voluntary green behavior (VGB). Additionally, the quantitative approach restricts deeper exploration of qualitative factors that may influence green behavior.